(untitled) (Journal of the College of Basic Education, 2020)
The truce in comparative Islamic jurisprudence One of the basic necessities of Islamic law is the concern for human life in all its aspects. It decided on provisions that would preserve its life and achieve happiness in this world and in the Hereafter. These provisions included the relationship of the Muslim man with his Lord and himself and those around him whether Muslims or non-Muslims. The most important topics of comparative Islamic political jurisprudence is the truce, which came to protect the Muslims, secure the borders of the Islamic State, and to prepare the conditions for preparing and preparing the kit, and neutralizing some enemies in order to devote themselves to the greatest enemy and to provide the appropriate atmosphere for spreading the call